The Effect of Digital Technology and Corporate Social Responsibility (CSR) on the Financial Performance of Manufacturing Companies with Financial Flexibility Moderation - Ula, Nada An Nur; Imronudin (Journal of Governance, Taxation and Auditing, 2026)
The development of digital technology is now an integral part of modern business strategies and is driving transformation in the manufacturing sector. Companies are increasingly expected to engage in continuous Corporate Social Responsibility (CSR) initiatives as part of maintaining constructive interactions with their stakeholders. This research investigates how digital technology adoption and CSR practices influence financial performance, while also assessing whether financial flexibility moderates these relationships, using a sample of manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The study employs a quantitative associative design with purposive selection, resulting in 125 observed firms. Data were processed using Moderated Regression Analysis (MRA) with Eviews 13. The findings reveal that digital technology does not exert a meaningful or positive contribution to financial outcomes, as its effect is negative and statistically insignificant. In contrast, CSR activities demonstrate a significant positive association with financial performance. Financial flexibility itself is shown to negatively and significantly affect financial performance. Moreover, financial flexibility fails to enhance the influence of digital technology on financial performance but does amplify the impact of CSR. Overall, the evidence indicates that CSR initiatives, when supported by robust financial flexibility, can serve as a strategic asset that elevates organizational performance and strengthens competitive positioning.